(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
Currently, urgent challenges such as the acceleration of technological progress, resource scarcity, globalization, and sustainability are forcing companies to redefine their manufacturing processes and create products that reduce waste, preserve resources, and reduce emissions and harmful pollutants through a wide range of strategies and practices. Therefore, this research aims to use the green innovation approach to promote sustainable manufacturing, in light of the field problem represented by the weakness of the manufacturing approach aimed at meeting environmental requirements represented by sustainable manufacturing as a window that qualifies it to stay and continue in the competitive market, with the aim of promoting the dimensions of green innovation in the practices of the researched company, the Krongi group of companies. The importance of the research is reflected in the questions raised, one of the most important of which is: what is the level of the impact of green innovation on sustainable manufacturing in the researched company? Data was collected through a survey from a random sample of 92 managers and employees of Krongi Company for carbonated beverages, mineral water, and juices in Kirkuk. The response rate was (96.84%) with 92 survey forms that were statistically analyzed using SPSS Ver-28. Several conclusions were reached, the most important of which was the validity of the assumptions included in the research through verifying the existence of a significant correlation between the research variables and the presence of a significant positive effect of green innovation and its dimensions on sustainable manufacturing, which reflects the interest of the researched company in adopting these dimensions and the compatibility of the nature of the company’s work and research variables. Several proposals were presented, the most important of which are disseminating the concepts of green innovation and sustainable manufacturing and their procedures among individuals working in the researched company, paying greater attention to embracing green innovation through searching for new and innovative technologies and methods that can help reduce waste, preserve resources, and reduce the environmental impact of manufacturing processes in the researched company, which enables companies to improve their competitiveness, reduce operating costs, and benefit from markets.